Skill-Biased Transition: The Role of Markets, Institutions, and Technological Change - Klara Sabirianova Peter (Institute for the Study of Labor (IZA), 2003)
This study attempts to explain why the transition to a market economy is skill-biased. It shows unequivocal evidence on increased skill wage premium and supply of skills in transition economies. It examines whether similar skill?favoring shifts in the Russian and U.S. economies are driven by the same set of factors. Our analysis elaborates on the model of alternative theories of the increased wage skill premium and then evaluates three main hypotheses: skill-biased technological change, the market adjustment hypothesis, and the institutional factor hypothesis. To test these hypotheses, the study uses unique linked employer-employee data that spans the 16 years of the Soviet and transition periods in Russia (1985-2000), with a special emphasis on data quality, measurement errors, and retrospective biases. The main conclusion is that there is no uni-causal and time-invariant explanation for skill-biased changes in wages and employment in the Russian economy. The increased skill wage premium has been driven mainly by institutional factors during the early period and by productivity and technological change during the late transition period, and reinforced by market adjustment of wage ratio to the true differences in labor productivity.
Keywords: J2; P3; P2; O57; O3; C8; J3; 330; technological change; wage inequality; human capital; transition; Russia; linked employer-employee data; Lohnstruktur; Qualifikation; Übergangswirtschaft; Wettbewerb; Institutionalismus; Technischer Fortschritt; Schätzung; Russland